(3GJNGP GdbQGQGJs - (3OhQdfZ cfOQSdjs; (3ecJHI dHfGf fGTQhfs ((3HjQhJs (3ecJHI dHfGf fGTQhfs, 2001)
(3jbOe gPG GdcJGH CSGdjH YdejI JhVM dc cjajI JMdjd hHfGA CSdhH UfY GdbQGQ GdNGU Hc hcjajI JfajP GdCacGQ HaYGdjI(B. (3jbhe GdfU GdhGVM hGdQShe GdJhVjMjI HJZWjI cGaI LhGfH UfY GdbQGQ GdQSej hZjQ GdQSej(B. (3Jecfc GdbhGFFe GdHSjWI GdNGUI HGdeQGLYI ef GdEYOGO GdJGe WhGd YedjI UfY GdbQGQ(B. (3Jbhe GdCTWGd GdJhVjMjI GdSgdI Gdage HYQV eNJda GdHOGFd GdNGUI HGdCOGA ceG JhaQ dc gPg GdCTcGd CeKdI YXjeI GdaGFOIs
(3jhQc HQSs
(3GdfU JQLe Gdi GdYQHjI ef GddZI GdGfLdjRjIs
1 2 10 13 14 21
Keywords: (3EOGQI GdCaQGOs; (3GJNGP GdbQGQGJs; (3GdbQGQGJ GdEOGQjIs